Association of plasma sphingosine-1-phosphate levels with disease severity and prognosis after intracerebral hemorrhage - Yang, Xuan; Wang, Kaixin; Shen, Ping; Zhou, Tong; Xu, Yudi; Chen, Yufei; Li, Yanfei; Yao, Yaobing; Gong, Zhe; Duan, Ranran; Jing, Lijun; Jia, Yanjie (Frontiers in Neurology, 2024)
Purpose: Sphingosine-1-phosphate (S1P) is a signaling lipid involved in many biological processes, including inflammatory and immune regulatory responses. The study aimed to determine whether admission S1P levels are associated with disease severity and prognosis after spontaneous intracerebral hemorrhage (ICH). Methods: Data of 134 patients with spontaneous ICH and 120 healthy controls were obtained from Biological Resource Sample Database of Intracerebral Hemorrhage at the First Affiliated Hospital of Zhengzhou University. Plasma S1P levels were measured. Regression analyses were used to analyze the association between S1P levels and admission and 90-day modified Rankin scale (mRS) scores. Receiver operating characteristic (ROC) curves assessed the predictive value of S1P levels for ICH severity and prognosis.Results: Patients with ICH exhibited elevated plasma S1P levels compared to the control group (median 286.95 vs 239.80 ng/ml, P<0.001). When divided patients into mild-to-moderate and severe groups according to their mRS scores both at admission and discharge, S1P levels were significantly elevated in the severe group compared to the mild-to-moderate group (admission 259.30 vs 300.54, P< 0.001; 90day 275.24 vs 303.25, P<0.001). The patients were divided into three groups with different concentration gradients, which showed significant statistical differences in admission mRS scores (3 vs 4 vs 5, P<0.001), 90-day mRS scores (2.5 vs 3 vs 4, P<0.001), consciousness disorders (45.5% vs 68.2% vs 69.6%, P=0.033), ICU admission (29.5% vs 59.1% vs 89.1%, P<0.001), surgery (15.9% vs 47.7% vs 82.6%, P<0.001), intraventricular hemorrhages (27.3% vs 61.4% vs 65.2%, p<0.001) and pulmonary infection (25% vs 47.7% vs 84.8%, P<0.001). Multivariate analysis displayed that S1P level was an independent risk factor for disease severity (OR=1.037, 95% CI=1.020-1.054, p<0.001) and prognosis (OR=1.018, 95% CI=1.006-1.030, p=0.003). ROC curves revealed a predictive value of S1P levels with an area under the curve of 0.7952 (95% CI=0.7144-0.8759, p<0.001) for disease severity and 0.7105 (95% CI=0.6227-0.7983, p<0.001) for prognosis. Conclusion: Higher admission S1P is associated with worse initial disease severity and 90-day functional outcomes in intracerebral hemorrhage.